2010
DOI: 10.1007/s10529-010-0293-x
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic differentiation of human mesenchymal stem cells: a comparison between micromass and pellet culture systems

Abstract: High-density cell culture is pivotal for the chondrogenic differentiation of human mesenchymal stem cells (hMSCs). Two high-density cell culture systems, micromass and pellet culture, have been used to induce chondrogenic differentiation of hMSCs. In micromass culture, the induced-cartilage tissues were larger, more homogenous and enriched in cartilage-specific collagen II but the fibrocartilage-like feature, collagen I, and hypertrophic chondrocyte feature, collagen X, were markedly decreased compared to thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
166
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(184 citation statements)
references
References 19 publications
(26 reference statements)
10
166
0
Order By: Relevance
“…In particular, a number of studies have shown that at 14 days, MSC differentiation and subsequent collagen type II gene expression was evident in the presence of TGF-β (Lee et al, 2008, Lisignoli et al, 2005, Bosnakovski et al, 2006, Park et al, 2009. Pellet culture systems are believed to be ideal culture environments to induce chondrogenesis due to the cell-cell contact which mimics the high cell density of embryonic cartilage development and maintains a chondrocytic phenotype (Fan et al, 2008, Chang et al, 2008, Zhang et al, 2010. A study comparing pellet culture and 3-dimensional culture showed that there was a significant increase in collagen type II expression on pellet cultures than on alginate and chitosan beads at day 14 (Bernstein et al, 2009).…”
mentioning
confidence: 99%
“…In particular, a number of studies have shown that at 14 days, MSC differentiation and subsequent collagen type II gene expression was evident in the presence of TGF-β (Lee et al, 2008, Lisignoli et al, 2005, Bosnakovski et al, 2006, Park et al, 2009. Pellet culture systems are believed to be ideal culture environments to induce chondrogenesis due to the cell-cell contact which mimics the high cell density of embryonic cartilage development and maintains a chondrocytic phenotype (Fan et al, 2008, Chang et al, 2008, Zhang et al, 2010. A study comparing pellet culture and 3-dimensional culture showed that there was a significant increase in collagen type II expression on pellet cultures than on alginate and chitosan beads at day 14 (Bernstein et al, 2009).…”
mentioning
confidence: 99%
“…This highlights the distinct differences that exist between ASCs and ESCs in terms of chondrogenic differentiation, and gives an insight into the potential complexity of generating chondrocytes from PSCs. Chondrogenic differentiation of EBs has been achieved via various culture methods, such as pellet or micromass culture [71] methods, also used for cartilage generation using primary chondrocytes and MSCs [76].…”
Section: Chondrogenesis In Ebsmentioning
confidence: 99%
“…Chondrogenic and hypertrophic-chondrogenic differentiation conditions Unless otherwise stated, 250,000 hBMSCs were cultured either alone as micromasses 45,46 or encapsulated in HA, FB, or their combinations. All samples were treated with chondrogenic conditioned media for 14 days.…”
Section: Weight Lossmentioning
confidence: 99%